Library Management in Enhancing Student Learning Motivation at SMP Negeri 1 Mangoli Tengah - Masuku, Mardiani; Sangaji, Radian M. (Civiliza Publishing, Indonesia., 2025)
Literacy is a basic competency that every student must have to compete in the challenging digital world. This study aims to discuss how library management can contribute to increasing student learning motivation at SMP Negeri 1 Mangoli Tengah. This research method uses a descriptive qualitative approach and was conducted at SMP Negeri 1 Mangoli Tengah, Sula Islands Regency, in November–December 2024. The study subjects included the principal, vice principal, librarian, teacher, and students. The study results indicate that although the school library has limitations, such as the absence of professional librarians, limited budget, basic facilities, and manual cataloging systems, library management that is applied simply but consistently has significantly contributed to student learning motivation. The appointment of teachers as library managers, implementing a